Discursividade, poder e autoria em raps brasileiros e portugueses : arenas entre a arte e a vida - Moreira, Tatiana Aparecida (Universidade Federal de São Carlos, 2016)
In this study, we aim at analyzing Racionais MC's group and rapper MV Bill raps, in order to examine how power operates in the instance of production of discourse, specifically in the construction of authorship, comparing them with the Mind da Gap group‟s and rapper Boss AC‟s Portuguese raps. To do this, we use as a theoretical and methodological scope studies of Michel Foucault (1995, 2002b, 2004, 2013) about the relationship among discourse, power and resistance, to ascertain the mode of production of these raps, as well as Bakhtin Circle‟s concepts (1995, 2003, 2010b, 2013) on dialogism, responsive-active attitude, authorship, surplus of vision / exotopy, to examine the specificities of the construction of authorship in Brazilian and Portuguese raps. Therefore, in a specific detailed chapter, we carry on about the listed theoretical concepts. The corpus selection based on the listed albums (Nada como um dia após o outro, 2002, by Racionais MC's group; Causa e Efeito, 2010, by rapper MV Bill; Matéria Prima, 2008, by group Mind da Gap; Preto no Branco, 2009, by rapper Boss AC) represent a phase in which the artists had already established their careers. The research also presents a contextualization of the Hip Hop Movement from the United States to Brazil and Portugal. In addition, the concepts of popular urban culture are discussed from Bakhtin (2010a, 2010b), Canclini (2002, 2006), Certeau (2001, 2003), Mayol (2005) and Hall (2003, 2004) perspectives. After the joints performed which culminated in the analysis of the raps, we conclude that the specificities for the construction of authorship in Brazilian and Portuguese raps can be summarized as follows: i) in the rap style that presents peculiarities; ii) the style that distinguishes the work in groups or individually; iii) the dialogue between the spheres of ethics and aesthetics.
Keywords: Poder; Autoria; Raps brasileiros; Raps portugueses; Power; Authorship; Brazilian raps; Portuguese raps; LINGUISTICA, LETRAS E ARTES::LINGUISTICA